Prothrombin Determination by Means of a Chromogenic Peptide Substrate - Axelsson, G; Korsan-Bengtsen, K; Waldenström, J (Thrombosis and Haemostasis, 1976)
A two stage method to determine prothrombin with the chromogenic peptide substrate benzoyl-phe-val-arg-p-nitroanilide has been worked out. Citrated plasma (10 μl) was diluted in 600 μl tris buffer, pH 8.2, ionic strength 0.18 and activated with 250 μl of a commercial rabbit brain-lung thromboplastin. After 325 s incubation at 37° C 200 μl of a 1 mM solution of the chromogenic substrate was added and the increase in absorbance was recorded in a LKB-Beckman 8600 enzyme analyzer. A reading time of 1 minute (including a delay of 20 s) was used which permitted 55 analyses per hour to be carried out. An approximate linear relationship was found between ΔA/min and dilutions of normal plasma in prothrombin deficient plasma. The method is insensitive to variations of factors V, VII and X. Less than 10 % of normal plasma was needed to “normalize” plasmas deficient in factor V or VII or X.A group of 99 dicoumarol treated patients and 23 normal subjects has been investigated using the present method and compared with a factor II-VII-X determination method. A correlation coefficient of 0.95 was found.